Game-theoretic Interference Coordination Approaches for Dynamic Spectrum Access - Xu, Yuhua; Alagan, Anpalagan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
Written by experts in the field, this book is based on recent research findings in dynamic spectrum access for cognitive radio networks. It establishes a game-theoretic framework and presents cutting-edge technologies for distributed interference coordination. With game-theoretic formulation and the designed distributed learning algorithms, it provides insights into the interactions between multiple decision-makers and the converging stable states. Researchers, scientists and engineers in the field of cognitive radio networks will benefit from the book, which provides valuable information, useful methods and practical algorithms for use in emerging 5G wireless communication.
Keywords: Telecommunication; Computer engineering; Computer networks .; Computer science -- Mathematics; Communications Engineering, Networks; Computer Engineering and Networks; Mathematical Applications in Computer Science; Microwaves, RF Engineering and Optical Communications